2005
DOI: 10.1089/mdr.2005.11.75
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial Infection Caused by Methicillin-ResistantStaphylococcus aureusin Palestine

Abstract: This report presents the prevalence of Palestinian isolates of methicillin-resistant Staphylococcus aureus (MRSA) in nosocomial infections and their antibiotic resistant pattern. A total of 321 clinical isolates of S. aureus were identified from different patients. The prevalence of methicillin resistance among S. aureus isolates was 8.7% (28 isolates). Resistance rates of MRSA to other antibiotics were as follows: 82.1% resistant to erythromycin, 67.9% to clindamycin, 64.3% to gentamicin, and 32.1% to ciprofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 14 publications
(22 reference statements)
4
17
0
Order By: Relevance
“…During the study, MRSA was found to be resistance to ciprofloxacin (65%), trimethoprimsulfamethoxazole (71%), clindamycin (89%) and erythromycin (88%). Similarly, Adwan et al 44 reported that up to 82.1% of nosocomial MRSA isolates were resistant to erythromycin and therefore, the macrolides cannot be considered first line therapy for serious Staphylococcal infections.…”
Section: Discussionmentioning
confidence: 99%
“…During the study, MRSA was found to be resistance to ciprofloxacin (65%), trimethoprimsulfamethoxazole (71%), clindamycin (89%) and erythromycin (88%). Similarly, Adwan et al 44 reported that up to 82.1% of nosocomial MRSA isolates were resistant to erythromycin and therefore, the macrolides cannot be considered first line therapy for serious Staphylococcal infections.…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial susceptibility patterns of the MRSA isolates are a cause for concern as an extremely high rate (above 82%) of resistance to penicillin G, erythromycin, clindamycin, ciprofl oxacin, gentamicin, cefotaxime, and sulfamethoxazole-trimethoprim was observed, a fi nding mirrored elsewhere [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…These practices might, in part, explain previous findings in Palestine that the prevalence of Methicillin-resistant staphylococcus aureus (MRSA) was the highest among isolates associated with upper respiratory specimens [2]. Unfortunately, inappropriate antibiotic practices have been previously reported in both hospital and community settings in Palestine.…”
Section: Af Sawalha / Self-medication With Antibiotics: a Study In mentioning
confidence: 99%